Operationalizing ulul albab on a spiritual leader: A case of TV AlHijrah Malaysia - Abdul Wahid, Nur Kamariah; Sabian, Nur Arfifah Abdul; Sarif, Suhaimi Md. (Asian Journal of Islamic Management (AJIM), 2022)
Purpose – The purpose of the paper is to explore on how the leadership of TV AlHijrah Malaysia, counter the economic crisis brought by Covid19 pandemic that they have succeeded in creating tv program like My QuranTime which led them to be awarded for ASEAN Inspiring Award Winner 2021 Innovation, Inspire, Creativity, the top ASEAN Award 2021. The interest of the paper is to understand how the transposition of spiritual leadership into Islamic leadership model could be explained practically. Methodology – The paper adopts qualitative research approach by employing interviews as the research instruments for the interest of the paper to go into in-depth understanding as well as to get the explanation on the leadership style of the leader of the organization Findings – The paper discovered that a new emerging element define as ulul albab has become the main contributor in explaining the transposition od spiritual leadership into Islamic leadership model element by explaining the elements of human capital aspects. Simultaneously, the findings have also able to explain the performance of the subject during such crisis in terms of the ability to transform the followers as well as organizational performances Implications – Potentially all Muslim leaders could improve their understanding of Islamic leadership from the lenses of spiritual leadership on taking the organization towards the desirable outcomes, covering the elements of organizational as well followers’ performance.Originality – The paper is believed to be with the original value as it only focuses on explaining the transposition of spiritual leadership into Islamic leadership model, by focusing on one specific organization, namely TV AlHijrah, that the emergence of ulul albab in explaining the human capital is seen as among the contribution.